P2-S7.03 Pregnancy and contraceptive experiences of women living with HIV in Mexico. (10th July 2011) - van Dijk, M; Wilson, K; Contreras, X; Ettenger, A; Fukuda, H D; García, S
Abstract : Background: In Mexico new HIV infections are occurring increasingly in women, but little is known about the experiences of women with HIV/AIDS seeking sexual and reproductive healthcare. Methods: In four states we conducted in-depth interviews with HIV-positive women who were pregnant or had been pregnant within the last 5 years. Participants were recruited through hospitals and clinics providing HIV care and through NGOs providing health and social services for people living with HIV. Results: Participants reported that the information and care they received were inadequate and influenced more by their providers' personal opinions than by their own fertility desires. They experienced provider discrimination and pressure to use particular contraceptive methods. HIV specialists and OB/GYNS differed significantly in practice, with HIV specialists focusing on prevention and condom use while OB/GYNS focused on long-acting or permanent methods of contraception. Due to gaps in contraceptive counselling and options many women had unplanned pregnancies while others resorted to sterilisation or abstinence. Furthermore, few women received adequate prenatal HIV care and counselling on pregnancy options. Conclusions: The health sector seems to focus narrowly on disease prevention and treatment lacking a holistic approach to women's wellbeing. The experiences of women living with HIV/AIDS reveal discrepancies between policy and practice in Mexico as manifested in gaps and inconsistency in healthcare services and even failures to respect patient confidentiality and human rights. The health sector should improve the integration of HIV and sexual and reproductive healthcare through cross-training HIV specialists and OB/GYNS, and by continued sensitisation of all providers on the topic.